Caracterização morfológica das inflorescências e infrutescências e visitantes florais do açaí preto (euterpe oleracea) e das etnovariedades (euterpe spp.). - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2008)
Açaí is one of the main resources of agribusiness in the state of Pará, which generates a source of income for the riverside community that lives from the collection and commercialization of the fruit and palm heart, however new alternatives of consumption can be obtained with ethnovarieties. The present work aimed to know the morphological structure of the inflorescences and infructescence and the floral visitors of the black açaí (Euterpe oleracea Mart.) and the ethnovarieties white, sword, tinga and una (Euterpe spp.). The collection of inflorescences and infructescences of açaí black, white and sword occurred on the island of Combu, municipality of Belém, Pará and the pistillate flowers of açaí tinga and infructescences of açaí una in the municipality of Abaetetuba and described according to Vidal & Vidal (1995) and Uhl & Dransfield (1987). The diameter of the fruits of açaí black (46 fruits), espada, white (50), uma (35) and tinga (50) were measured with a caliper and the values correlated in the Bioestat 5.0 program. The floral visitors were collected with entomological net during the daytime period in the black açaí on the island of Combu in Benfica, municipality of Benevides and on the research campus of the Museu Paraense Emílio Goeldi; for the white açaí and espada only on the island of Combu and packed in glass containers containing 70% alcohol, transported to the Zoology Coordination of the Museu Paraense Emilio Goeldi for identification and with the aid of specialized literature the possible behavior in the flowers was determined. The results showed differences in the flowers regarding the coloration of the petals, type of anther, shape of the pistilodium, shape and coloration of the stigma and number of flowers, in the diameter and coloration of the fruits. As for the floral visitors, 9 orders, 19 families, 28 genera and 38 species were identified for Euterpe oleracea; 6 orders, 6 families, 11 genera and 15 species for açaí espada and 4 orders, 5 families, 8 genera and 8 species for açaí branco with a higher frequency of species in the orders Coleoptera and Hymenoptera whose behavior can characterize them as probable polioizadores and pilharadores. It is of fundamental importance to continue the taxonomic and ecological studies on the genus Euterpe, in order to frame the ethnovarieties as new taxonomic categories.
Morphological characterization of inflorescences and infructescences and floral visitors of black açaí (euterpe oleracea) and ethnovarieties (euterpe spp.).
Keywords: Euterpe; Morfologia; Biologia reprodutiva; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL